Price discrimination in merger review in South Africa: Implications of recent case precedent - Leuner, Rahma (Southern Centre for Inequality Studies (SCIS) University of the Witwatersrand, Johannesburg, 2025)
Mergers have the potential to give firms access to more data from which to draw insights about consumers. This may help firms to better discern which consumers are price insensitive or captive, or exhibit behavioural biases, that they can exploit by charging them higher prices or nudging them towards higher priced options. Based on recent case precedent, we believe that the transfer or sharing of data or techniques in mergers involving price-discriminating firms may be sufficient for meeting the requirement of merger-specificity without there needing to be an increase in market power. Recent local case precedent also provides insight into when mergers impact on just a small group of consumers are likely to matter. It suggests that the competition authorities in the country should be more concerned where consumers are vulnerable and where access to the services/products is particularly important to this group.
Keywords: Merger; discrimination; personalise; antitrust; competition; SDG-10: Reduced inequalities